Selling the drama a political economic analysis of ABS-CBN's promo materials for primetime soap operas - Sedilla, Danie Rose Villanueva (2006)
This study titled "SELLING THE DRAMA: A Political Economic Analysis of ABS-CBN's Promo Materials for Primetime Soap Operas", analyzes promo materials produced for primetime soap operas Hiram, Krystala and Spirits as a away to investigate how a network giant like ABS-CBN strategizes its promos to market or "sell" its primetime soap operas. Using the political economy framework, this study explains the political economic implications which figure in the production and distribution of promo materials for primetime soap operas. In so doing, it delves deeper into the creative and production process of soap opera promos, from conceptualization to production to distribution.
"March 2006."
Thesis (M.A. Broadcast Communication)--University of the Philippines Diliman.
Keywords: Advertising -- Television programs -- Philippines; Soap operas -- Economic aspects -- Philippines; ABS-CBN (Television station : Quezon City).